Multimedia writing procedures for musical composition, seven case studies (2022)
The purpose of this article is to describe the multimedia writing (MW) procedures that have proven to be effective in resolving some of the difficulties faced by composers in: 1. notation of timbre, 2. notation of new performance modes, 3. notation of new vocal techniques, 4. notation of a tonal language in a score, 5. notation of the instructions for the use of the computer programs contained in the work, 6. synchronization of the oral tradition musicians with the audio recordings, and 7. time reduction during the learning of the work. To address these issues, we used MW in six "experiments" —composition projects designed to answer specific questions about notation. These experiments and other subsequent projects allowed us to confirm our findings. In our experiments, MW was a set of procedures that allowed information to be represented in different ways simultaneously. The information can be text, sound, still or moving images, among others. These procedures can be used to record a message with the aim of saving it and transferring it from the composer to the performer. The results obtained demonstrated the effectiveness of MW in overcoming the current limitations of the Western music writing system (WMWS).